A side-hinged paddle wavemaker - Sulisz, W.; Zdolska, A. (Archives of Mechanics, 2023)
Theoretical investigations were conducted to study the generation of transient nonlinear water waves by a novel side-hinged paddle wavemaker. A 3D nonlinear solution was derived in a semi-analytical form by applying eigenfunction expansions and FFT. The solution was applied to study the features of nonlinear waves generated by a side-hinged paddle wavemaker. The results show that nonlinear terms in the free-surface boundary conditions and in the kinematic wavemaker boundary condition imply the modification of wave profiles so that wave troughs are flattered and crests are getting steeper and interaction effects between waves in a wave train increase. Moreover, these terms imply the modification of a wave spectrum. A train of originally very narrow-banded waves changes its one-peak spectrum to a multi-peak one. Theoretical results are in a fairly good agreement with experimental data. A reasonable agreement is observed between predicted and measured time series of free-surface elevations and the amplitudes of the corresponding Fourier series. The investigations show that a side-hinged paddle wavemaker is an attractive wave generation system. Simple and reliable boundary condition at the paddle enables verification of advanced 3D nonlinear models and accurate physical modeling of many phenomena where high accuracy of incoming wave properties are important.